The Templeton twins have an idea / 1. - Weiner, Ellis (Weiner, Ellis. Templeton twins, 2013)
Abigail and John, the Templeton twins, and their dog Cassie, foil a pair of inept kidnappers intent on stealing one of their father's newest inventions.